2022
DOI: 10.2147/cia.s388325
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement in Delirium Health Literacy in Older Adult Patients and Their Caregivers Attending a Geriatric Clinic

Abstract: Background: Delirium is a common medical condition that is highly prevalent in older adults who are at increased risk for its development with any illness, post-surgery or during hospitalization. The purpose of our study was to evaluate the health literacy of older adult patients and their caregivers about delirium, offer a brief educational intervention, and reevaluate their knowledge post intervention. Materials and Methods:We conducted a quality improvement project, focused on delirium health literacy in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…This rigorous multi‐method systematic review has identified that barriers to health professionals recognizing and managing delirium are significant issues that compromise safety and effectiveness of care for older adults during an acute hospital stay, with consequences also for patients' family and friends, clinicians and healthcare organizations. This finding is concerning particularly given the focus and investment in quality improvement in national (e.g., GMRC, 2022; Vardy & Thompson, 2020) and international (e.g., Azhar et al., 2022) healthcare contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This rigorous multi‐method systematic review has identified that barriers to health professionals recognizing and managing delirium are significant issues that compromise safety and effectiveness of care for older adults during an acute hospital stay, with consequences also for patients' family and friends, clinicians and healthcare organizations. This finding is concerning particularly given the focus and investment in quality improvement in national (e.g., GMRC, 2022; Vardy & Thompson, 2020) and international (e.g., Azhar et al., 2022) healthcare contexts.…”
Section: Discussionmentioning
confidence: 99%
“…
I have read with interest the paper by Azar et al, about the improvement in delirium health literacy they achieved in older adult patients and their caregivers, while attending a geriatric clinic. 1 The improvement in delirium literacy close to complete competence is valuable indeed, and it is worthily warranted, as its need is apparent.Yet I am just concerned about the statistical tool Authors adopted in their analysis. I suggest to verify if their results still persist using a different test.
…”
mentioning
confidence: 99%